2019
DOI: 10.15666/aeer/1703_55715581
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Herbage Yield and Nutritive Value of Eight Forage Crop Species

Abstract: Determining nutritional quality of indigenous forage species constitutes prerequisite to improve the productivity of ruminants. This research was carried out at the research field of the Agricultural Research and Application Center of Igdır University, Turkey in consecutive two years (2015 & 2016) to evaluate the herbage yield and nutritive value of eight forage species having diverse genetic make-up. Eight forage species such as Kentucky bluegrass (Poa pratensis var. Geromino), Perennial rye-grass (Lolium pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
(21 reference statements)
0
8
0
1
Order By: Relevance
“…Similarly, sorghum-lima bean intercropping in a 80:20 ratio yielded a higher biomass by reducing the interference of weeds and preventing the leaching of nutrients. It was also inferred that mixed seeding remained more effective in N transfer to cereal than row or relay intercropping systems [10]. Barley-faba bean mixed seeding in a 70:30 seed-blending ratio produced 52% higher herbage yield [11].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, sorghum-lima bean intercropping in a 80:20 ratio yielded a higher biomass by reducing the interference of weeds and preventing the leaching of nutrients. It was also inferred that mixed seeding remained more effective in N transfer to cereal than row or relay intercropping systems [10]. Barley-faba bean mixed seeding in a 70:30 seed-blending ratio produced 52% higher herbage yield [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, it was concluded that time and crop stages of previous harvestings determine the plant height of Egyptian clover [52,55]. Pertaining to the number of capsules and seeds per capsule, it was found that the source-sink relationship remained dynamic and varied by the crop stage and harvest management [53,56,57]. In addition, it was revealed that after the harvesting of berseem clover, shoots became the prime sinks, which were supplied assimilates by the roots and leftover crowns, which served as assimilate sources.…”
Section: Experiments 2 321 Yield Attributes and Seed Yieldmentioning
confidence: 99%
“…The highest CF, ADF, and NDF of hay were related to hay. A number of studies have shown that earthworm compost is a stable and successful combination of soil pH, which can improve the availability of soil nutrients [24,25]. In investigation of forage barley intercropping with legumes, Strydhorst et al [26] revealed that intercropping with legumes crops produced higher protein than barley monoculture.…”
Section: Hay Vs Silagementioning
confidence: 99%